Inovasi Aplikasi siCANTIK Cloud Terhadap Pelayanan Pengurusan Surat Izin Kesehatan Di DPMPTSP Aceh Barat - Mursyida Mursyida; Nellis Mardhiah (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2022)
This study aims to find out how the services that occur in the West Aceh DPMPTSP by applying the siCANTIK Cloud application innovation to the management of health permits. This research method is using descriptive qualitative. Data collection techniques were carried out by means of interviews, observation, and documentation. The results of this study indicate that the innovation of the siCANTIK Cloud application in managing health permits at DPMPTSP Aceh Barat has not run optimally. The policies implemented are in accordance with the SOP and can be well received by the community, with the innovations applied can be beneficial for the community as recipients of services and also for agencies. However, in the processing of permits, people still experience difficulties because the siCANTIK Cloud application often experiences errors, people also have to wait until their registration verification is sent by email in order to continue their registration.